Alisol A 23,24-diacetate improves LPS-induced acute lung injury through the IL-17A/NF-κB signaling pathway - Yuhan Zhang; Pengli Guo; Mengnan Zeng; Denghui Zhu; Ziyu Zhang; Mengdie Luo; Yi Chao; Fangzhuo Chang; Weisheng Feng; Xiaoke Zheng (Chinese Medicine, 2026)
Abstract Objective This study utilized the multi-model validation method to confirm that Alisol A 23,24-diacetate (AAD) can improve LPS-induced acute lung injury (ALI) through the IL-17A/NF-κB signaling pathway, providing experimental data support for preclinical research. Methods Mice were given drugs by gavage continuously for 3 days, and then LPS was instilled into trachea to establish the model of acute lung injury. Subsequently, the lung pathological sections, lung function, the levels of oxidative stress and apoptosis, the metabolic levels in lung tissue and serum, and the levels of immune cells and inflammatory factors in each group of mice were detected. Then, the differentially expressed genes were screened based on the GEO database, and molecular docking combined with PCR technology was employed to investigate the potential pathogenesis of acute lung injury. Next, in vivo mouse models and in vitro lung organoid models were utilized, combined with Western blot and immunofluorescence techniques, to validate the proteins associated with the IL-17A/NF-κB signaling pathway. The binding of AAD to IL-17A protein was detected by cellular thermal shift assay (CETSA). Finally, the Beas-2B cell model combined with IL-17 agonist (SR0987) and IL-17 antagonist (Brodalumab), as well as the zebrafish model coupled with the methods of IL-17A gene silencing and overexpression, were employed to validate the mechanism of action underlying the intervention of AAD in LPS-induced ALI. Results AAD significantly ameliorated lung injury and lung function in a mouse model of LPS-induced ALI, modulated metabolic and immune disorders in ALI mice, and suppressed the release of inflammatory factors. The results from GEO database analysis, molecular docking, PCR, WB, immunofluorescence and CETSA, demonstrated that AAD ameliorates LPS-induced ALI via the IL-17A/NF-κB signaling pathway. In Beas-2B cells, AAD significantly suppressed the LPS-induced elevation of ROS and apoptosis levels, reduced the protein expression of IL-17A and p-NF-κB p65, and decreased the levels of inflammatory factors, exerting a comparable therapeutic effect to that of the IL-17 antagonist. However, the therapeutic efficacy of AAD was abrogated following the addition of an IL-17 agonist. In the experiment of zebrafish, AAD significantly enhanced the sports activity of zebrafish and inhibited the levels of IL-17A and inflammatory factor RNA. However, the therapeutic efficacy of AAD was abrogated following IL-17A gene overexpression. Conclusion AAD improves LPS-induced ALI through the IL-17A/NF-κB signaling pathway.